Intersecting Identities: Exploring Urban Aboriginal Women's Experiences of Accessing Care - Van Herk, Kimberley A (University of Ottawa (Canada), 2010)
The purpose of this master's thesis is to explore intersections within Aboriginal womens' descriptions of their experiences of accessing care in an urban context, and to explicate how service provider's perceptions of women's identity featured in their care encounters. This thesis is divided into three chapters. The first chapter provides a background on access to care for Aboriginal women living in urban contexts, outlines the methodology of the primary study, and explores the intersectionality paradigm used to complete the secondary analysis done for this study. The second chapter describes the results of the study. It begins by providing a general overview of the major themes and subthemes, followed by two manuscripts that have been written for submission for publication in scholarly journals. The third chapter discusses how this study has contributed to new knowledge for nursing, as well as the implications for nursing education, research and policy.
Keywords: Health Sciences, Nursing.